Implementasi Putusan MK 31/PUU-X/2012 Jo. SEMA 4 Tahun 2016 Dalam Putusan Pengadilan TIPIKOR - Arqi Nur Mubarok; Wahyu Priyanka Nata Permana (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
The formulation of the problem in this research is: 1. Who is the institution that has the authority to determine/declare state losses based on Constitutional Court Decision Number 31/PUU-X/2012 jo. SEMA Number 4 in 2016? 2. How to implement the Constitutional Court Decision Number 31/PUU-X/2012 jo. Sema Number 4 of 2016 regarding the calculation of state financial losses in court decisions for criminal acts of corruption in Indonesia? The author uses normative legal research methods. Whereas the results of the discussion on the first formulation are regarding which norm is higher, namely the Constitutional Court Decision, so that it can be seen that the institution that has the authority to determine/declare state losses is the BPK or BPKP, while the discussion on the second problem formulation is regarding the implementation/enforcement regarding the calculation of state financial losses in the decision. TIPIKOR trials are carried out by the BPK, BPKP and even by the judges themselves